(3QSGdI aj GdchGcHs - (3chTjGQ Hf dHGf GdLjdj, CHh GdMSf,J (B350 (3g` s
(3ChdgG (B:s
(3bGd LeYJ ai gPG GdcJGH ef CUhd UfGYI GdCMcGe hLedgG hGdWQjb Edi GdJUQa ajgG s
(3BNQgG (B:s
(3hfNJe GdebGdI GdQGHYI HgPG GdHGH hGdcJGH HgPg GdebGdI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdJGSYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B838s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs